Factors affecting the level of health care worker’s stigmatized and discriminatory attitude towards people living with HIV: A study at the Dr. Zainoel Abidin General Hospital, Banda Aceh, Indonesia - H. Harapan; Syarifah Feramuhawan; Hendra Kurniawan; Mohd. Andalas; Mohammad Bellal Hossain (Syiah Kuala University, 2011)
The aim of this study was to identify the level of health care worker`s (HCW) stigmatized and discriminatory (SD) attitude towards people living with HIV (PLHIV) and the factors that influenced this attitude. This research was conducted at the Dr. Zainoel Abidin General Hospital (RSUDZA) in Banda Aceh province of Indonesia. A cross-sectional study design was adopted for this research. Eighty nine HCWs were included in this study and they were selected purposively. Pearson correlation analysis, analysis of variance or independent sample t test analysis was used according to the type of data. We found that the level of SD attitude towards PLHIV in RSUDZA is high. Based on the Least Significant Difference Test, the average score of the answers between nurses and general practitioners and between nurses and medical students was significantly different(p=0.05). Pearson correlation analysis showed that the levels of SD attitude towards PLHIV was positively correlated with age (r=0.219, p=0.04) and irrational fear of HIV transmission (r=0.352, p=0.001) and negatively correlated with knowledge about HIV/AIDS (r=-0.336, p=0.001). Pearson correlation analysis also found that knowledge of HIV/AIDS negatively correlated with the irrational fear of HIV transmission (r=0.382, p=0.000). In addition, the level of SD attitude towards PLHIV was also associated with marital status of HCWs (p=0.020). Gender, education level, religion and the importance of religion in HCW lives wasn`t significantly affect to the level of SD attitude towards PLHIV in HCW. We concluded that the factors that influence the level of SD attitude towards PLHIV among the HCW are age, marital status, knowledge of HIV/AIDS, irrational fear of HIV transmission and HCWs occupations. To reduce SD attitude towards PLHIV among the HCWs, we recommend introducing some program to increase knowledge of HIV/AIDS